Invito alla Psicologia sociale - Spinosi, Nicola (Strumenti per la didattica e la ricerca, 2005)
The volume presents topics and authors (K. Lewin, M. Sherif, S. Moscovici, S. Milgram and H. Tajfel among others) that characterise social psychology in a specific sense, as a discipline that works on the situational dimension, looking into other terms to grasp in the "here and now" the articulation between individual and collective, also meaning the culture to which we belong. After giving a historical framework of the discipline in relation to the main psychological schools of the twentieth century (psychoanalysis, behaviourism, Gestalt theory, cognitivism, cultural psychology), the research methods and themes on which the action of social psychology is exercised are outlined.